Strategy to Strengthen the Income of Forest Farmers' Group on Coffee Commodities in Mekakau Ilir District, South OKU Regency - Jumroni; Munajat, Munajat; Permata Sari, Fifian (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This study aims to determine strategies for increasing the income of coffee farmers in Mekakau Ilir District, OKU Selatan Regency. The quantitative analysis used in this research is regression analysis. The results of this study in the form of a strategy to increase coffee farmers' income based on internal and external results showed that the main strategies are optimizing weaknesses and overcoming various threats by reducing land conversion by providing capital, reactivating Gapoktan, optimizing fertilizer use, overcoming the problem of increasing input prices to increase cooperation between extension workers and Gapoktan in Mekakau Ilir District, OKU Selatan Regency.Contribution to Sustainable Development GoalsSDG 1: No PovertySDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land